The rhetorical rise and demise of "democracy" in Russian political discourse. - Williams, David Cratis, 1955-; Young, Marilyn J., 1942-; Launer, Michael K. (Academic Studies Press, 2021)
"The essays in this book examine the arguments and rhetoric used by the United States and the USSR following two catastrophes that impacted both countries, as blame is cast and consequences are debated. In this environment, it was perhaps inevitable that conspiracy theories would arise, especially about the downing of Korean Air Lines Flight 007 over the Sea of Japan. Those theories are examined, resulting in at least one method for addressing conspiracy arguments. In the case of Chernobyl, the disaster ruptured the "social compact" between the Soviet government and the people; efforts to overcome the resulting disillusionment quickly became the focus of state efforts"--